Henry P. McKean Jr. Selecta - Grünbaum, F. Alberto; van Moerbeke, Pierre; Moll, Victor H.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Birkhäuser, 2015)
This volume presents a selection of papers by Henry P. McKean, which illustrate the various areas in mathematics in which he has made seminal contributions. Topics covered include probability theory, integrable systems, geometry and financial mathematics. Each paper represents a contribution by Prof. McKean, either alone or together with other researchers, that has had a profound influence in the respective area.
1.Personal Recollections -- 2.My Debt to Henry McKean -- 3.Henry McKean and Integrable Systems -- 4. Some Comments -- 5.Some Words from Three Students -- 6.Curvature and the Eigenvalues of the Laplacian -- 7.Hill's Operator and Hyperelliptic Function Theory in the Presence of Infinitely Many Branch Points -- 8.Book Reviews: Riemann Surfaces of Infinite Genus by J. Feldman, H. Knörrer, and E. Trubowitz -- 9.Fredholm Determinants and the Camassa-Holm  Hierarchy -- 10.Breakdown of the Camassa-Holm Equation -- 11.Rational Theory of Warrant Pricing -- 12.Geometry of KdV (1): Addition and the Unimodular Spectral Classes -- 13.Weighted Trigonometrical Approximation on R1 with Application to the Germ field of a Stationary Gaussian Noise -- 14.Brownian Local Times -- 15.Brownian Motions on a Half Line -- 16.The Spectrum of Hill's Equation -- Bibliography.
Keywords: Mathematics; Mathematics, general